2008
DOI: 10.1016/j.juro.2008.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Psychosocial Correlates of Symptoms Suggestive of Painful Bladder Syndrome: Results From the Boston Area Community Health Survey

Abstract: Purpose-The objective is to estimate the prevalence of symptoms suggestive of Painful Bladder Syndrome (PBS) defined as pain increasing as the bladder fills and/or pain relieved by urination for at least three months and its association with socio-demographics (gender, age, race/ethnicity, and socioeconomic status), lifestyle (smoking, alcohol consumption, physical activity) and psychosocial variables (sexual, physical, emotional abuse experienced as a child or as an adult, worry, trouble paying for basics, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 23 publications
2
30
1
3
Order By: Relevance
“…For instance, several studies administered surveys about prior diagnoses of IC/BPS or ‘prostatitis’, 1-6 or about current symptoms of IC/BPS 7, 8 or CP/CPPS. 2-6 Others have abstracted data from medical records.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, several studies administered surveys about prior diagnoses of IC/BPS or ‘prostatitis’, 1-6 or about current symptoms of IC/BPS 7, 8 or CP/CPPS. 2-6 Others have abstracted data from medical records.…”
Section: Introductionmentioning
confidence: 99%
“…Those percentages translated into 3.3 to 7.9 million women 18 years old or older with IC/PBS symptoms [4]. Other studies have estimated the prevalence of IC/PBS among men to be 2 to 5 times lower than in women [5], [6]. Symptoms of IC interfere with employment, social relationships, and sexual activity.…”
Section: Introductionmentioning
confidence: 99%
“…IC/PBS occurs mainly in women, with a prevalence estimated in different studies to be two to five times higher than in men (12,35). The most recent National Institutes of Healthfunded epidemiological study of IC/PBS in women in the United States (the Rand IC Epidemiology study) identified prevalences of 6.5% and 2.7% based on high sensitivity and high specificity criteria, respectively, for diagnosing IC/PBS (7).…”
mentioning
confidence: 99%